2019
DOI: 10.5223/pghn.2019.22.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Functions in Infants with Malnutrition; Relation with Long-chain Polyunsaturated Fatty Acids, Micronutrients Levels and Magnetic Resonance Spectroscopy

Abstract: PurposeMalnutrition may influence neurocognitive development in children by directly affecting the brain structural development, or indirectly by affecting the children's cognition experience. Malnutrition alters the cell numbers, cell migration, synaptogenesis, and neurotransmission due to inadequate availability of necessary micronutrients to support cell growth. We aimed to analyze neurocognitive development in infants with malnutrition and its association with long chain polyunsaturated fatty acids (LC-PUF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…El-khayat H et al used BSID II and found de inite neurodevelopment problem in malnourished children. Deviation from normal Tables 1 and 2 also increased with increasing severity of malnutrition in this study (El-khayat et al, 2007;Cakir et al, 2019).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…El-khayat H et al used BSID II and found de inite neurodevelopment problem in malnourished children. Deviation from normal Tables 1 and 2 also increased with increasing severity of malnutrition in this study (El-khayat et al, 2007;Cakir et al, 2019).…”
Section: Resultssupporting
confidence: 63%
“…Developmental evaluation is de ined as information on individuals' skills and potential (Cakir et al, 2019;Chopra and Sharma, 1992;Paul and Bagga, 2019). It is used to assess the existence of a developmental delay, to identify needs and strengths, to establish intervention approaches, to evaluate progress on signi icant developmental milestones and to serve as a basis for parental reporting (Paul and Bagga, 2019;Ke et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term dietary variation in selenium influences oxidative stress that impacts cognitive functions [14]. Total neurocognitive development in infants was positively associated with serum calcium levels [15]. Therefore, calcium supplementation may improve neurocognitive development in malnourished infants [15].…”
Section: Discussionmentioning
confidence: 99%
“…Total neurocognitive development in infants was positively associated with serum calcium levels [15]. Therefore, calcium supplementation may improve neurocognitive development in malnourished infants [15]. Low vitamin D status in pregnancy is associated with offspring language and motor development, particularly in young children [16].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it appears that a reduction in myocardial creatine significantly correlates with the clinical severity of heart failure [ 24 ], with tissue creatine put forward as an independent multivariate predictor of cardiovascular mortality in patients with failing hearts [ 25 , 26 ]. Tissue creatine levels were also diminished in the skeletal muscle and brain of patients with chronic respiratory failure [ 27 , 28 ], extracts from lung cancer patients [ 29 ], pancreatic parenchyma in patients with adenocarcinoma [ 30 ], in the brain of patients with hepatitis C and chronic HIV infection [ 31 , 32 ], and in the thalamus of infants with malnutrition [ 33 ], while suboptimal creatine levels are suggested in chronic kidney disease [ 34 ], and preterm birth [ 35 ]. Although the causes of the above conditions are different, they all share a disease-associated creatine deficit.…”
Section: Creatine Shortfall In Clinical Medicinementioning
confidence: 99%